“MY FIRST SEXUAL KNOWLEDGE” VIDEO-ANIMATION-BASED FOR THE PROTECTION OF CHILDREN AGED 4-6 YEARS FROM SEXUAL VIOLENCE - Zuhriyah, Siti; Ndari, Susianty Selaras (Journal of Early Childhood Education (JECE), 2021)
The purpose of this research is to develop media “my first sexual knowledge" based on animated videos for the protection of children from sexual violence aged 4-6 years. The research method carried out by the researcher is the method research and Development. The development used is qualitative and quantitative according to the model ADDIE which consists of four components: Analysis, Design, Development or Production, Implementation or Delivery and Evaluations. This video has been validated by media experts with the final assessment results of 98.75% and 97.58%. Besides being validated by media experts and material experts, this video has also been tested on a small scale on 16 children accompanied by parents with the results of 85.03% and 90.20% has been tested on a large scale on 34 children accompanied by parents. small and large scale trials are categorized as very good. Based on the results of research that has been carried out, the video my first sexual knowledge is a reference for educators and parents to provide education to children so that they are protected from acts of sexual violence.